Return to Troy : new essays on the Hollywood epic - Winkler, Martin M. (Metaforms, 2015)
Return to Troy presents essays by American and European classical scholars on the Director's Cut of Troy , a Hollywood film inspired by Homer's Iliad . The book addresses major topics that are important for any twenty-first century representation of ancient Greek myth and literature in the visual media, not only in regard to Troy : the portrayals of gods, heroes, and women; director Wolfgang Petersen's epic technique; anachronisms and supposed mistakes; the fall of Troy in classical literature and on screen; and the place of the Iliad in modern popular culture. Unique features are an interview with the director, a report on the complex filming process by his personal assistant, and rare photographs taken during the original production of Troy .